2013
DOI: 10.1007/s00595-013-0794-z
|View full text |Cite
|
Sign up to set email alerts
|

A close look at postoperative fluid management and electrolyte disorders after gastrointestinal surgery in a teaching hospital where patients are treated according to the ERAS protocol

Abstract: Postoperative registration of fluid charts is difficult, which results in incomplete charts. This has resulted in more attention being paid to recording the fluid balance at our institution. Concerning electrolyte disorders, we recommend prophylactic potassium administration. However, there is no reason to replace standard 0.9 % NaCl/glucose 5 % by Ringer's lactate, as the British guidelines advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Several methods of managing postoperative ileus (POI) in patients with colon cancer, such as no insertion of a nasogastric tube, epidural analgesia, oral magnesium oxide, and laparoscopic surgery, have been advocated [14][15][16][17]. Fluid management is also important for patients undergoing major gastrointestinal surgery [18]. LVR should be even less invasive surgery than laparoscopy-assisted colon resection, because it is a non-resectional technique and may reduce the stress response, leading to less POI.…”
Section: Discussionmentioning
confidence: 98%
“…Several methods of managing postoperative ileus (POI) in patients with colon cancer, such as no insertion of a nasogastric tube, epidural analgesia, oral magnesium oxide, and laparoscopic surgery, have been advocated [14][15][16][17]. Fluid management is also important for patients undergoing major gastrointestinal surgery [18]. LVR should be even less invasive surgery than laparoscopy-assisted colon resection, because it is a non-resectional technique and may reduce the stress response, leading to less POI.…”
Section: Discussionmentioning
confidence: 98%
“…[20] A previous study recommended prophylactic potassium administration for patients scheduled for gastrointestinal surgery. [21] Potassium can be administrated intravenously or orally. Intravenous potassium is suitable for severe hypokalemia and must be monitored under electrocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…73,74 One study of patients' fluid balance postoperatively under use of an ERAS protocol revealed no clinically significant fluid overload or electrolyte disturbances. 75 Careful monitoring of fluid status should be continued in the postoperative period to maintain fluid balance.…”
Section: Maintenance Fluidsmentioning
confidence: 99%